Challenges Of Global Economic Competition: The Singapore Response - Yeoh, Caroline (Asian Academy of Management (AAM), 1996)
Singapore attained internal self-government as a British colony in 1959, inheriting severe economic, social and political problems. The government's strategic response was to launch an industrialisation programme to attract manufacturing industries to Singapore. The first industrialisation strategy emphasized import-substitution, in expectation that the then proposed Malaysian common market would materialise.